Chronic cough management: Dealing with a sensation of mucus in the throat. Issue 4 (25th April 2013) - Ogawa, Haruhiko; Fujimura, Masaki; Takeuchi, Yasuo; Makimura, Koichi
Abstract Among the various types of laryngeal paresthesia, the results of the study with use of a newly developed cough‐related laryngeal sensation questionnaire suggested that a sensation of mucus in the throat (SMIT) can predict the presence of fungal colonization in chronic cough patients. Next to 'cough' or 'sputum', SMIT may become the third key clinical manifestation leading to successful prediction of the efficacy of antifungal therapy in chronic cough patients.